1982
DOI: 10.1128/iai.36.1.107-113.1982
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a high-affinity mechanism for acquisition of transferrin iron by Neisseria meningitidis

Abstract: Iron-starved meningococci grown at either pH 7.2 or 6.6 were capable of removing and incorporating iron from human transferrin by a saturable, cell surface mechanism that specifically recognized transferrin rather than iron. The maximum expression of the iron uptake system occurred after 4 h of iron starvation. The uptake of the iron was dependent upon a functioning electron transport chain and was sensitive to 60°C and trypsin. Cells grown under ironsufficient conditions were incapable of accumulating iron fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(93 citation statements)
references
References 23 publications
7
86
0
Order By: Relevance
“…Some pathogenic microorganisms extract iron directly from iron binding glycoproteins. Neisseria gonorrhoeae and N. meningitidis scavenge sufficient iron for growth from transferrin even at only 4% saturation [92] by a mechanism that is induced by iron restriction and dependent on a functional electron transport chain [93,94]. The process is highly specific for human transferrin.…”
Section: Utilisation Of Host Iron Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pathogenic microorganisms extract iron directly from iron binding glycoproteins. Neisseria gonorrhoeae and N. meningitidis scavenge sufficient iron for growth from transferrin even at only 4% saturation [92] by a mechanism that is induced by iron restriction and dependent on a functional electron transport chain [93,94]. The process is highly specific for human transferrin.…”
Section: Utilisation Of Host Iron Compoundsmentioning
confidence: 99%
“…Chicken ovotransferrin is not an iron source for Neisseria species [92], despite a high degree of homology with human transferrin [31], and in competitive solid phase dot binding assays rabbit, horse and bovine transferrins were unable to compete with human transferrin for binding to receptors [95]. Pathogenic Neisseria species also utilise human lactoferrin as an iron source [94][95][96][97], while most non-pathogenic species are unable to utilise either iron-binding protein [92,93,98]. The receptors for transferrin and lactoferrin in these species are distinct since neither protein is capable of blocking the binding of the other in solid phase dot binding assays [99,100].…”
Section: Utilisation Of Host Iron Compoundsmentioning
confidence: 99%
“…it has been shown that the availability of iron influences the virulent properties of Neisseria meningitidis [139][140][141]. Although Neisseria seems not to produce siderophores |142-144], Neisseria meningttidJs might acquire iron from transferrin [143][144][145] and iactofcrrin [146] through specific membrane receptors [147,148]. The receptor for transferrin is iron regulated, and seems to be highly specific for human transferrin [1471.…”
Section: Iron Acquisition From the Iron-binding Proteins Of The Hostmentioning
confidence: 99%
“…Most of the extracellular iron in the human body is bound by two glycoproteins, transferrin (Tf) in serum and lactoferrin (Lf) in mucosal and other biological fluids. Unlike the Enterobacteriaceae, Neisseria menin-gitidis does not produce extracellular siderophores in order to obtain iron uptake [1] but have developed high-affinity mechanisms based on iron-regulated outer membrane protein receptors which directly and specifically bind Tf, thereby allowing iron transport into the bacterial cell [2][3][4]; the mechanism of iron uptake from transferrin is presently unclear [5,6].…”
Section: Introductionmentioning
confidence: 99%